Coexistent Breast Cancer and Essential Thrombocythemia: How We Addressed the Therapeutic Challenges - Karan Seegobin; Bharatsinh Gharia; Satish Maharaj; Lara Zuberi (Case Reports in Hematology)
Essential thrombocythemia (ET) occurring with breast cancer is uncommon; the therapeutic approach varies and poses a challenge. A 65-year-old female presented to us after being diagnosed with hormone positive, HER2-negative infiltrating ductal carcinoma. She had a platelet count of 600 thou/cu mm. Her JAK2 mutation was positive. Bone marrow biopsy showed increased megakaryocytes. She was diagnosed with ET in the setting of breast cancer. She underwent breast conservation surgery after which aspirin was resumed. Anticipating thrombocytopenia during chemotherapy and given the absence of data combining hydroxyurea with standard chemotherapy used for breast cancer, we felt it prudent to delay cytoreductive therapy for her ET until after completion of breast cancer treatment. Her average platelet count during chemotherapy was 480 thou/cu mm with the lowest being 377 thou/cu mm. Her platelet count remained at goal between 300 and 350 thou/cu mm after four months of hydroxyurea.